2014
DOI: 10.1007/s10585-014-9688-8
|View full text |Cite
|
Sign up to set email alerts
|

T-DM1, a novel antibody-drug conjugate, is highly effective against uterine and ovarian carcinosarcomas overexpressing HER2

Abstract: Introduction Ovarian and uterine carcinosarcoma (CS) are characterized by their aggressive clinical behavior and poor prognosis. We evaluated the efficacy of trastuzumab-emtansine (T-DM1), against primary HER2 positive and HER2 negative CS cell lines in vitro and in vivo. Methods Eight primary CS cell lines were evaluated for HER2 amplification and protein expression by FISH, immunohistochemistry, flow cytometry and qRT-PCR. Sensitivity to T-DM1-induced antibody-dependent-cell-mediated-cytotoxicity (ADCC) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 34 publications
(47 reference statements)
1
39
0
Order By: Relevance
“…In Nicoletti’s study, T-DM1 and T were similarly effective in inducing strong ADCC against CS overexpressing HER2 at 3+ levels. In contrast, T-DM1 was dramatically more effective than T in inhibiting cell proliferation and, more importantly, in reducing tumor formation in CS xenografts overexpressing HER2 with a significantly longer survival when compared to T (44). Unfortunately, the activity of TDM-1 was evlauted in this study only against HER2/neu 3+ CS by IHC and c-erbB gene amplified endometrial cancer cell lines.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In Nicoletti’s study, T-DM1 and T were similarly effective in inducing strong ADCC against CS overexpressing HER2 at 3+ levels. In contrast, T-DM1 was dramatically more effective than T in inhibiting cell proliferation and, more importantly, in reducing tumor formation in CS xenografts overexpressing HER2 with a significantly longer survival when compared to T (44). Unfortunately, the activity of TDM-1 was evlauted in this study only against HER2/neu 3+ CS by IHC and c-erbB gene amplified endometrial cancer cell lines.…”
Section: Discussionmentioning
confidence: 80%
“…In an effort to optimize the use of HER2 blockade in the next phase of CS treatment and meaningfully alter patient outcomes, multiple groups including our own, have investigated the frequency of HER2 expression in uterine and ovarian CS with a reported range of overexpression of 25%–56% (3234, 43, 44). Along these lines, Nicoletti et al, recently compared the activity of T-DM1 and Trastuzumab (T) against HER2 positive and negative primary CS cell lines in vitro followed by developing a supportive CS in vivo model.…”
Section: Discussionmentioning
confidence: 99%
“…T-DM1, a combination of traztuzumab (anti-HER2/ neu) and mertansine (microtubule polymerization inhibitor) was recently demonstrated by Nicoletti et al [51] to be highly effective at targeting and killing HER2/neu OCS in a mouse model. Guzzo et al [52] reported HER2/neu gene and protein expression in primary carcinosarcoma cell lines and demonstrated trastuzumab-mediated antibody-dependent cellular cytotoxicity against uterine and ovarian carcinosarcomas in vitro.…”
Section: Targeted Therapymentioning
confidence: 99%
“…In another study by the GINECO group, HER 2 was found to be amplified in 6.8% of patients [93]. Many preclinical studies have shown the efficacy of HER2 targeting agents in ovarian cell lines [94][95][96]. In the clinical setting, a phase II trial was undertaken, where the eligible patients had 2/3+ IHC score for HER2.…”
Section: Her2 Targeting Agentsmentioning
confidence: 99%
“…So, they concluded that the role of trastuzumab in ovarian cancer is limited because of the low levels of expression of HER2 as well as the low response rates [97]. Trastuzumab emtansine (T-DM1) has also shown to be effective in ovarian cancer cell lines, but there is lack of any meaningful clinical data [95].…”
Section: Her2 Targeting Agentsmentioning
confidence: 99%